Gut microbiome: A potential indicator for predicting treatment outcomes in major depressive disorder - Dong, Zaiquan; Shen, Xiaoling; Hao, Yanni; Li, Jin; Xu, Haizhen; Yin, Li; Kuang, Weihong (Frontiers in Neuroscience, 2022)
Major depressive disorder (MDD) is one of the most common and heterogeneous mental illnesses with unsatisfactory therapeutic outcomes. The factors that affect and predict the treatment outcome of MDD are still unclear. Here, we characterize microbial composition and function during treatment using antidepressants in MDD patients based on 16 S rRNA sequencing and metabolomics. We found that the microbial signatures in baseline between responder and non-responder groups were significantly different. The non-responder group was mainly characterized by increased relative abundances of Actinobacteria (phylum), Christensenellaceae (family), Eggerthellaceae (family), Adlercreutzia (genus), and Christensenellaceae-R-7-group (genus) relative to responder group. We found that the gut microbiota of the responder group and the non-responder group were significantly different before and after treatment, and dynamic changes of the species showed differences, especially at the genus level, between the responder and non-responder groups before and after treatment. Moreover, we identified 20 metabolites responsible for discriminating between responder and non-responder groups. Those differential metabolites were mainly apparent in lipid metabolism (cholestane steroids and steroid esters). Significantly, Eggerthellaceae and Adlercreutzia formed strong co-occurring relationships with some metabolites, indicating alternations of gut microbiome and metabolites as potential mediators in efficiency of antidepressant treatment. Overall, our study demonstrated that the alterations of microbial compositions and metabolic functions might be relevant to the different response to antidepressants, which sheds new light on the mechanisms of their efficacy.